Talking History with Professor Verene Shepherd - Nationwide 90 FM
This programmme was done for a history talk carried out by Professor Verene Shepherd on Nationwide 90 Fm. The event was done to facilitate CXC and Cape Students in their preparation for their history examinations.
Keywords: Programme -- Jamaica